Junction Analysis Using Sidra Intersection - Alqerbi, Adel Abdulwahid (Universiti Teknologi PETRONAS, 2017)
As we all know junctions are the most important part of the road, because most of the activate appear there such as speed, emissions, accident etc. the purpose of this study is to do analysis on Malaysia junctions using Sidra intersection, Sidra intersection is a software package used for intersection and network capacity, level of service and performance analysis by traffic design, operations and planning professionals. Sidra Intersection provides a many intersection and network performance measures and a number of alternative Level of Service (LOS) methods and LOS determine acceptable intersection and network design. Standard performance measures such as delay, queue length and number of stops as well as measures to help with environmental impacts and economic analysis are provided.